Diagnostic lab-on-a-chip systems at the doctor's office: a survey amongst German physicians in routine medical care. (September 2015) - Gebauer, Alexander; Muehlan, Holger; Hoffmann, Wolfgang
Aim & method : We conducted a physician's survey to ask the potential 'users' about needs and options for lab-on-a-chip systems (LOCs) in their office to provide information about the feasibility of the implementation of LOCs into the healthcare system.Results : From a random sample of 300 questionnaires, 61 were returned. The willingness to use LOCs is very high (91.9%) and only 6.5% mentioned that they would continue to use conventional tests strictly in the future. Reliability is seen as the most important prerequisite for a successful implementation (85%).Conclusion : Generally, physicians are very open-minded and positive regarding the implementation of LOCs in routine care.